Polypoid basal cell carcinoma: A scoping review - Po-Chien Wu; Ying-Xiu Dai; Yu-Ju Chou; Yun-Ting Chang; Chih-Chiang Chen; Sheng-Hsiang Ma (Wolters Kluwer Medknow Publications, 2022)
Polypoid basal cell carcinoma (BCC) is characterized by a stalk connecting the tumor and skin surfaces, with neoplastic cells restricted in the polypoid zone microscopically. A thorough review of polypoid BCC is still lacking. Thus, we performed this scoping review to investigate the clinical manifestations, dermoscopic features, histopathology, treatment, and prognosis of polypoid BCC. A literature search was conducted in the PubMed, Embase, Web of Science, and Cochrane databases until December 23, 2021. Studies reporting at least one patient with polypoid BCC following the pathology and clinical criteria were included. A total of 47 studies with 54 patients with solitary polypoid BCC and 13 patients with multiple polypoid BCCs were included. Solitary polypoid BCC occurred at a relatively younger age, with an equal sex ratio. These tumors most commonly presented as red or flesh-colored pedunculated papules and were commonly distributed over nonsun-exposed areas. Most tumors were managed with excision, and recurrence or metastasis was seldom reported. Most patients with multiple polypoid BCCs had basal cell nevus syndrome and presented with generalized distributed, flesh-colored, or brown papules mimicking skin tags. Typical dermoscopic features of BCC could still be observed in these lesions, including arborizing vessels, blue-gray globules, and ovoid nests, which could aid in early diagnosis. In conclusion, polypoid BCC is a distinct variant of BCC with pedunculated morphology. Physicians should be aware of polypoid BCC and may use dermoscopy to aid in early diagnosis and treatment.